Deter, detain, dehumanise : the politics of seeking asylum - Sharples, Rachel; Briskman, Linda (Emerald Publishing Limited, 2024)
Under a pretext of humanitarian response to people seeking asylum, nation states are increasingly introducing barriers to prevent entry for those seeking safety and security. Documenting the systemic politicisation of the right to seek asylum in Australia, a process that has been hailed as a model for other parts of the world, Deter, Detain, Dehumanise examines how the right to seek asylum has become a political tool of deterrence, detention and dehumanisation. Bringing together leading academics across criminology, geography, law, political science, social work and sociology, this edited collection provides an understanding and critical assessment of Australian government policy as a series of systems, structures and operations that seek to normalise the detention and deterrence of those seeking asylum, explicitly defying Australia's international human rights obligations. Complemented by shorter, creative writings by refugees with lived experience of detainment at Australia's behest, chapters pursue an overtly political and innovative conceptual approach to the politicisation of seeking asylum, offering new insights into its structural framings. Taken together, this body of work examines how Australia has politicised the right to seek asylum, to the detriment of asylum seekers and refugees as well as Australian citizens, and tentatively offers hope on how we might seek to normalise, legitimise and re-humanise the processes.
Keywords: Asylum, Right of -- Australia.; Refugees -- Political aspects -- Australia.; Social Science, Refugees.; Refugees and political asylum.; elektronické knihy; electronic books